Circadian clocks regulate cardiac arrhythmia susceptibility, repolarization, and ion channels. (April 2021) - Delisle, Brian P; Stumpf, John L; Wayland, Jennifer L; Johnson, Sidney R; Ono, Makoto; Hall, Dalton; Burgess, Don E; Schroder, Elizabeth A
Graphical abstract: The graphic symbolizes the well-known observation that cardiac electrophysiology changes at different times of day. Clinically, sudden cardiac death is shown to have a time of day increase incidence for certain types of heart disease. To better understand how environment and gene interactions contribute to cardiac electrophysiology, several investigators have generated transgenic mouse models that disrupt circadian clocks in different tissues including the heart. These studies show a role for functional circadian clocks in regulating heart rate, the development of dilated cardiomyopathy, cardiac repolarization, and cardiac ion channels. Daily changes in the incidence of sudden cardiac death (SCD) reveal an interaction between environmental rhythms and internal circadian rhythms. Circadian rhythms are physiological rhythms that alter physiology to anticipate daily changes in the environment. They reflect coordinated activity of cellular circadian clocks that exist throughout the body. This review provides an overview of the state of the field by summarizing the results of several different transgenic mouse models that disrupt the function of circadian clocks throughout the body, in cardiomyocytes, or in adult cardiomyocytes. These studies identify important roles for circadian clocks in regulating heart rate, ventricular repolarization, arrhythmogenesis, and the functional expression of cardiac ion channels. They highlight a new dimension in the regulation of cardiac excitability and represent initial forays into understanding the complexities of how time impacts the functional regulation of ion channels, cardiac excitability, and time of day changes in the incidence of SCD.